2011
DOI: 10.1253/circj.cj-11-0185
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Protective Effect of Human Atrial Natriuretic Peptide in Cardiac Surgery - "hANP Shot" in Clinical Safety Trial -

Abstract: Background:We studied low-dose human atrial natriuretic peptide (hANP) infusion therapy during cardiac surgery and reported the cardiac and renal protective effects. The efficacy of a bolus injection of hANP (the "hANP shot") simultaneously with induction of cardioplegia has been proven in animal experiments. In the present study the clinical effects of this "hANP shot" were examined. Methods and Results:The subjects were 67 patients undergoing Coronary artery bypass grafting. At the time of inducing cardiople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…NP (nesiritide) failed to show benefit in acute decompensated heart failure, but its cardioprotective effect, particularly against ischemic injury, warrants further investigation. 78 …”
Section: Resultsmentioning
confidence: 99%
“…NP (nesiritide) failed to show benefit in acute decompensated heart failure, but its cardioprotective effect, particularly against ischemic injury, warrants further investigation. 78 …”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, to date no such drug is approved for use in man . On the other hand, the potential of natriuretic peptides to initiate destruction of the glycocalyx may well explain the unequivocal or poor long term results obtained in clinical studies aiming to improve heart function or to limit the consequences of myocardial infarction by applying recombinant human BNP (nesiritide) or ANP (carperitide) .…”
Section: Clinical Conditions With Signs Of Glycocalyx Degradationmentioning
confidence: 99%
“…11 In previous clinical studies, a significant increase in plasma cGMP levels was reported during continuous lowdose hANP infusion (0.02-0.05 μg · kg -1 · min -1 ), which was associated with improved hemodynamic parameters such as pulmonary capillary wedge pressure, right atrial pressure, cardiac index, left ventricular stroke work index, and systemic…”
Section: Article P 2144mentioning
confidence: 92%